Pemanfaatan Tepung Ampas Tahu dengan Penambahan Pasta Kacang Merah dalam Formulasi Snackbar - Putri Septya Ningrum Chaniago; Suko Priyono; Nur Endah Saputri (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
Snack bar is a food product made from a combination of ingredients that are bound together by a binding agent. One type of snack bar is a protein bar. A potential primary ingredient for making high-protein snack bars is tofu dregs.